Using Cohort Fertility Indicators to Assess and Predict the Effectiveness of Demographic Policies - Archangelsky, Vladimir Nikolayevich; Dzhanaeva, Natalia Georgievna (Economy of Regions, 2015)
The analysis of fertility indicators for cohort gives an adequate assessment of the effectiveness of demographic policy and measurement of perspective fertility rates for demographic forecasts, eliminating the impact of the shifts in birth timing in their dynamics. Traditionally, the average number of children born in a cohort is delivered in population census results. The assessed values of these indicators can be obtained by using age-specific fertility rates. The practical experience suggests that for Russia on the whole, these calculated estimates are undeniably correct. On the regional level, their accuracy raises doubts, as female groups for which age-specific fertility rates are provided, can markedly differ year after year because of interregional migration, and vary from population census data. The authors attempt to consider the applicability of such approach to fertility rate estimations for a cohort in the regions of the Ural Federal District. For some regions, summed age-specific fertility rates produce reasonable results. It is thus expedient to take as a basis the average number of born children for cohort according to the population census and add annual age-specific fertility rates for the post-census period. The analysis of average numbers of children born in a cohort (as for the beginning of 2014) has shown positive shifts both for Russia on the whole and for the Ural Federal District regions. The majority of females, which reproductive behavior may be affected by public support measures provided for families with children and introduced from 2007, have not finished their child-bearing process yet. However, it is already possible to report at least about the stabilization of the average number of the second and third births, starting with the cohorts born in the early 1970s. Thus, the shares of females given birth to the second child among those given birth to the first child, and the shares of mothers given birth to the third child among those given birth to the second, were not simply stabilized but have already increased. At the same time, the available statistical and sociological data do not provide evidence of shifts in birth timing toward earlier births of the second and subsequent children. More likely, it is arguable that the births postponed for a long time were fulfilled.